Connecting the dots between extreme ideologies, "parent choice," and education privatization in Alberta and Canada - Ganshorn, Heather (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
Privatization of public education in North America has long been influenced by two schools of conservative thought: neoliberalism, which seeks to create a marketplace for public services in which individuals choose the option they judge to be in their best interests and government's role is limited as much as possible to simply funding these choices; and neoconservatism, which believes that education should seek to uphold traditional religious and social values. These two strains are divided in terms of their view of how much control government should seek over education, but united in their agreement that funding should "follow the student" to the option of the parents' choice. Recently, far-right conservative groups in the U.S. and Canada have been inciting a moral panic over "gender ideology" in schools, and in particular transgender students. Under cover of this moral panic and the accompanying call to recognize "parent rights," the right is organizing to gain greater influence over public education through legislation and through the election of conservative candidates to school boards, even as it seeks greater privatization options for families who wish to opt out of public education. While this trend has been noticeable in Alberta for some time, it appears to be spreading to the rest of Canada as well.